Operational control system of civil aicraft airborne equipment and scientific basis of its formation - S. V. Kuznetsov (Научный вестник МГТУ ГА, 2021)
The system of operational control (SOC) of civil aircraft (CA) airborne equipment incorporates onboard equipment, as an object of control, means and programs of operational control, maintenance personnel of an operating enterprise, carrying out procedures using control means and organizing processes of operational control for the specified objects using control programs. Quality of A/C onboard equipment SOC becomes obvious in the process of operational control. Operational control is a set of processes for determining the technical condition (TC) of objects of control (OC) at the various operational stages: in flight, during operational maintenance (pre-flight and post-flight control), and periodic maintenance, after dismantling equipment from board. The process of determining OC TC of includes control, diagnostics, forecasting and recovery. The process of operational control is characterized by reliability of control – the property of TC control, which determines the extent of display objectivity as a result of monitoring the actual OC TC. Based on the SOC analysis as an object of research, the analysis of the problem of its forming and updating as well as the developed hierarchy of criteria for the effectiveness of interacting systems, the general problem will be formulated as follows: on a given set of parameters of onboard equipment SOC, let us determine the parameter values so that the system costs in the process of operational control reach minimum while performing all the required tasks and observing all the limitations for own parameters of the system as well as indicators of its technical efficiency.